Pirossequenciamento de alta cobertura da região hipervariável 1 do Vírus da Hepatite C - Yamasaki, Lílian Hiromi Tomonari [UNESP] (2014)
Hepatitis C is a major public health problem. New HCV antiviral drugs were released on market on 2010; however, excluding for genotype 1, the most used therapy used currently is still based on Interferon (IFN) and Ribavirin. Nowadays, genotype 3 is the one with the highest rate of treatment failure. Viral genome variability is one of the factors that lead in therapy failure. HCV presents a high mutability during replication course, implicating in arising of intra-host variants called quasispecies. The hypervariable region 1 (HVR1) from envelope protein presents as quasispecies and may be related to IFN therapy resistance. Resistant quasispecies may not represent majority of variants population in the host, therefore, in these cases traditional sequencing techniques are unable to detect. For detection of minority quasispecies, ultra-deep pyrosequencing (UPDS) is a reliable and efficient tool, being able to detect even variants with frequency <1% in the population. Regarding this issue, we determined HVR1 quasispecies from 14 patients infected with HCV genotype 3 using the UPDS approach. In total, 64,400 HVR1 sequences were obtained from pre-therapy sample. From these sequences, 27,398 ones with high quality were filtered. Genetic distance and Shannon entropy values were not related to therapy outcome. These sequences were analyzed using median-joining networks and Bayesian population structural analysis. These analysis identified samples with different structures, from high conserved (one sub-population) to high stratified ones (6 sub-populations). Networks analysis also confirmed this result. Mutations exclusive for a type of response of therapy were identified along HVR1. Amino acid sequences indicated that this region presents conserved structure, even if sequence and physical and chemicals properties seem flexible. Especially in turns and coils positions, this conservation seems notable. Potential epitopes positions are concentrated ...